CLASSROOM MANAGEMENT IN ENHACING STUDENT LEARNING MOTIVATION AT MADRASAH IBTIDAIYAH - rahma, rahma (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Education plays a strategic role in shaping the future of the nation by improving the quality of human resources both physically and spiritually. Teachers, as the main actors in the educational process, hold vital roles as instructors, mentors, motivators, facilitators, and classroom managers. Teacher professionalism is a determining factor in achieving the development of students' cognitive, affective, and psychomotor aspects. This study aims to analyze the approaches, strategies, and methods of classroom management in enhancing students’ learning motivation at MIN 1 Denpasar. A qualitative approach was employed using field research methods. Data were collected through observation, interviews, and documentation, while data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data condensation, data display, and drawing and verifying conclusions. The results of the study show that the classroom management approach at MIN 1 Denpasar is predominantly humanistic, focusing on the development of self-discipline and active student participation. Management strategies include individual attention, the formulation of shared rules, the provision of rewards, educational humor, and the creation of a conducive learning environment. The methods applied encompass group discussions, cooperative learning, positive behavior reinforcement, the use of interactive media, and the provision of creative challenges